2004
DOI: 10.1086/381925
|View full text |Cite
|
Sign up to set email alerts
|

A Multiyear Photometric Study of IC 348

Abstract: The extremely young cluster IC 348 has been monitored photometrically over five observing seasons from 1998 December to 2003 March in Cousins I with a 0.6 m telescope at Van Vleck Observatory. Twenty-eight periodic variables and 16 irregular variables have been identified. The variability study is most sensitive for stars with I < 14:3 mag; at that brightness level, we find that 24 of the 27 known pre-main-sequence (PMS) cluster members in the monitored field are variables, illustrating the value of photometri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
107
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(125 citation statements)
references
References 35 publications
15
107
2
1
Order By: Relevance
“…This bias towards WTTS has been reported by other studies in the literature (e.g., Cohen et al 2004;, and it is assumed to be present in all the studies comparing the rotation of CTTS and WTTS. In the present study, a direct consequence of it is that the size of the CTTS sample is much smaller than the size of the WTTS sample.…”
Section: Does Cygob2 Corroborate the Disk-locking Scenario?supporting
confidence: 50%
“…This bias towards WTTS has been reported by other studies in the literature (e.g., Cohen et al 2004;, and it is assumed to be present in all the studies comparing the rotation of CTTS and WTTS. In the present study, a direct consequence of it is that the size of the CTTS sample is much smaller than the size of the WTTS sample.…”
Section: Does Cygob2 Corroborate the Disk-locking Scenario?supporting
confidence: 50%
“…Presumably, it is indicative of a bursting history of star formation in the galaxies giving rise to damped systems. However, it is important to realise that a variety of recent observations suggest that the α-enhancement exhibited by metal-poor stars of the Milky Way may in fact be the exception rather than the rule -it is generally not seen in dwarf spheroidal and dwarf irregular galaxies Shetrone et al 2003;Tolstoy et al 2003;Aloisi et al 2003), in old stars of the Large Magellanic Cloud (Hill et al 2000), in DLAs (this paper), in some Galactic halo stars with large orbits (Nissen & Schuster 1997), and in the globular cluster Pal 12 which may originally have been part of the Sgr dSph galaxy (Cohen 2004). The challenge now is to incorporate this rapidly growing set of abundance measurements into a comprehensive picture of the chemical evolution of galaxies.…”
Section: Discussionmentioning
confidence: 75%
“…As far as the point (iii) is concerned, we remark that rotation may be mass-dependent over the range of masses included in our sample. For instance, Cohen et al (2004) found that the G-type PMS stars in IC 348 rotate faster than the K5-M2 stars. Thus, if our targets have a mass distribution markedly different from the subsample of ONC stars with M > 0.7 M , this could affect the observed period distribution.…”
Section: Rotation Period Distributionmentioning
confidence: 99%